Weibull absorption

I have a question about Weibull absorption shown in the Pumas tutorial.
I understood that,
absorbed amount = F x Dose x (1 - exp(-(λ x t)^γ)) when Weibull absorption is applied.
And Depot' = -(λ x γ) x (t x λ)^(γ-1) x Depot.
But in the tutorial, it was written that
Depot' = -(1 - exp(-(Ka∞ * t)^γ)) x Depot.
I am wondering if those equations are the same. To my understanding, Ka will have an upper bound of 1 when we use the equation from the tutorial.
Could you please explain how to derive the equation in the tutorial?
Thank you!